1991
DOI: 10.1037/0033-2909.110.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating as escape from self-awareness.

Abstract: This article proposes that binge eating is motivated by a desire to escape from self-awareness. Binge eaters suffer from high standards and expectations, especially an acute sensitivity to the difficult (perceived) demands of others. When they fall short of these standards, they develop an aversive pattern of high self-awareness, characterized by unflattering views of self and concern over how they are perceived by others. These aversive self-perceptions are accompanied by emotional distress, which often inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

126
1,311
6
38

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,935 publications
(1,508 citation statements)
references
References 274 publications
126
1,311
6
38
Order By: Relevance
“…As reflected in the continuum of differences between diagnostic groups, the increasing levels of pathology from obese nonbingers to bulimics suggest a pattern that is consistent with the premise put forth by Heatherton and Baumeister (1991) and supported by Stice and colleagues (1996) in their dual pathway model. Although Heatherton and Baumeister (1991) did not address the spectrum of eating disorders or the continuity/discontinuity perspective per se, they proposed that the motivation for bingeing comes from a need to escape self-awareness.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As reflected in the continuum of differences between diagnostic groups, the increasing levels of pathology from obese nonbingers to bulimics suggest a pattern that is consistent with the premise put forth by Heatherton and Baumeister (1991) and supported by Stice and colleagues (1996) in their dual pathway model. Although Heatherton and Baumeister (1991) did not address the spectrum of eating disorders or the continuity/discontinuity perspective per se, they proposed that the motivation for bingeing comes from a need to escape self-awareness.…”
Section: Discussionsupporting
confidence: 80%
“…Although Heatherton and Baumeister (1991) did not address the spectrum of eating disorders or the continuity/discontinuity perspective per se, they proposed that the motivation for bingeing comes from a need to escape self-awareness. The bingeing serves as a short-term escape by allowing an individual to narrow her focus to the immediate present and potentially avoid painful affect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies found that binge eating alleviates negative feelings in PERFECTIONISM AND PSYCHOLOGICAL NEED FRUSTRATION 23 the short term and helps to suppress extreme emotions (Munsch, Meyer, Quartier, & Wilhelm, 2012). Binge eating might thus be seen as a way to escape from negative self-awareness and from the need frustrating experiences (Heatherton & Baumeister, 1991). Second, need frustrating experiences require energy from an individual, which might cause ego-depletion.…”
Section: Psychological Need Frustration and Binge Eating Symptomsmentioning
confidence: 99%
“…There has been some interesting research into the cognitive mediators of dieting and compulsive eating (Heatherington & Baumeister, 1991;Jansen, Merckelback, Osteerlaan, Tuiten, & Vanderhout, 1988;Polivy & Herman, 1991;Ruderman, 1985). There is some evidence that restrained eaters overeat after the disruption of self-control of caloric intake (Ogden & Wardle, 1991;Ruderman, 1986).…”
Section: Review Of the Literaturementioning
confidence: 99%